Women who have undergone hysterectomy: a retrospective study - Condor, Celeste Maria V. (Animo Repository, 1996)
The uterus has become the favored target of surgical abuse in the US, Canada and Australia in the last three decades. A marked increase in the number of hysterectomies is believed to be due to the greater use of elective indications in Canada. However, there is no data at present for the Philippines. In a review of issues concerning reproductive health and reproductive rights in local literature, it has been found that there is an overemphasis of fertility regulation. Reproductive health and reproductive rights are in fact a broader concept than controlling fertility. With reproductive health and reproductive rights in mind, the increasing trend of hysterectomies lead us to think of whether these are still women's choices or that of her doctor's. A review of the hospital records of Vicente Sotto Memorial Medical Center in Cebu City for two years (1990 and 1995) shows that there is a 45 percent increase in the number of hysterectomies. The study tackled the problem of identifying factors that influence a woman's decision to undergo hysterectomy, with particular attention to the process of decision-making and the consequences of the decision on sexuality, general health, the performance of tasks, and the woman's relationship with significant others. The women in the study were identified from the medical records of the VSMMC. They were located in the community and interviewed on their experiences with hysterectomy. From these records and with the help of some snowball technique, a total of 30 women were interviewed. From there, 7 doctors who performed the hysterectomies were also identified. They were given a 3- page questionnaire to answer regarding their views on hysterectomy and patient management. The mean age of women who underwent hysterectomy was 44.43 years. Mean age at operation was 42.53 years. The mean educational attainment of the women is college level, and a large majority are Roman Catholics. The women affirmed their belief in the ability and authority of the doctor to cure diseases and to decide what is best for the patient, but they also thought that a person has the right to decide for oneself even when ill.Several factors were considered to influence women's decisions to undergo hysterectomy. They are: her knowledge of illness, the presence of a support system, her individual preference and autonomy, and her physician's preferences. More than half of the women thought they were severely sick during the time they were experiencing the symptoms of their problem. Majority of the women's reactions to the advise of undergoing hysterectomy was fear of surgery, because of financial constraints. All the women reported that they had available support for them to undergo hysterectomy. A significant number of women was found to be autonomous in the decisions they made regarding sexuality and contraceptive choice.The women responded positively toward their hysterectomy. Seventeen affirmed that they were the ones who decided to undergo hysterectomy. The preop problems felt by the women, all disappeared after hysterectomy. Postoperatively, the married women's sexual activities were much affected by hysterectomy.